Can differences in benefits affect group investment into irrigation projects? Experimental evidence from Northern Ghana - Edward Asiedu; Elena Groß (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2017)
Particularly in sub-Saharan Africa, agriculture is predominantly rain-fed and, therefore, prone to unstable weather conditions and less productive than in other regions of the world. Increasing the efficiency and sustainability of farmer groups and cooperatives is of primary importance to many policy makers in developing countries. Experimental studies have suggested that the privileged person in a group would voluntarily provide the public good in social dilemma situations, while those with lower benefits would free-ride. Using a framed lab-in-the-field experiment complemented by a detailed household survey in rural Ghana, we examine how asymmetries in benefits and real wealth levels impact farmers' behavior and group outcomes. We find that efficiency concerns (i.e. higher group returns) outweigh inequality concerns. Thus, the implication is that higher group benefits and heterogeneous within-group benefits reduce strategic uncertainty and enhance cooperation in agricultural settings of subsistence farmers. Finally, aside from the group-level effects, we show that farmers with smaller potential benefits and those who live in poor households contribute even more than the resource rich. The results indicate that, as much as interventions are aimed at saving the poor, the poor contribute much to save themselves. These results remain robust, controlling for a long list of covariates including socioeconomic characteristics, loss aversion and inequality aversion. The results overall have implications for structuring farmer groups and the provision and maintenance of both public goods and common-pool resources in poor countries.
Keywords: C93; D31; D63; O13; Q15; Q2; 330; asymmetric benefits; lab-in-the-field experiments; group financing; farmer cooperatives; development financing; irrigation in Sub-Saharan Africa; Ghana